2016
DOI: 10.1139/gen-2015-0218
|View full text |Cite
|
Sign up to set email alerts
|

Improving herpetological surveys in eastern North America using the environmental DNA method

Abstract: Among vertebrates, herpetofauna has the highest proportion of declining species. Detection of environmental DNA (eDNA) is a promising method towards significantly increasing large-scale herpetological conservation efforts. However, the integration of eDNA results within a management framework requires an evaluation of the efficiency of the method in large natural environments and the calibration of eDNA surveys with the quantitative monitoring tools currently used by conservation biologists. Towards this end, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 74 publications
4
82
0
Order By: Relevance
“…We have demonstrated eDNA metabarcoding is a highly sensitive tool for monitoring T. cristatus alongside the wider biological community, corroborating other comparisons of eDNA metabarcoding and qPCR for single‐species monitoring (Lacoursière‐Roussel et al., ; Schneider et al., ). Despite reduction in single‐species detection, eDNA metabarcoding revealed a wealth of biodiversity information and could enable more effective freshwater monitoring networks and better understanding of community structure and ecosystem function alongside T. cristatus monitoring (Biggs, von Fumetti, & Kelly‐Quinn, ).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…We have demonstrated eDNA metabarcoding is a highly sensitive tool for monitoring T. cristatus alongside the wider biological community, corroborating other comparisons of eDNA metabarcoding and qPCR for single‐species monitoring (Lacoursière‐Roussel et al., ; Schneider et al., ). Despite reduction in single‐species detection, eDNA metabarcoding revealed a wealth of biodiversity information and could enable more effective freshwater monitoring networks and better understanding of community structure and ecosystem function alongside T. cristatus monitoring (Biggs, von Fumetti, & Kelly‐Quinn, ).…”
Section: Discussionsupporting
confidence: 84%
“…Conversely, the passive approach uses conserved primers (i.e., primers with binding sites that are shared across multiple taxa, and flank a region of highly variable DNA sequence that enables discrimination between these taxa) and PCR to sequence whole communities with high‐throughput sequencing (HTS), termed eDNA metabarcoding (Deiner et al., ; Shaw, Weyrich, et al., ; Taberlet, Coissac, Pompanon, Brochmann, & Willerslev, ; Valentini et al., ). Passive eDNA monitoring is particularly attractive to ecologists for biodiversity assessment as a means to detect entire species assemblages alongside rare or invasive species (Blackman et al., ; Lacoursière‐Roussel, Dubois, Normandeau, & Bernatchez, ). However, this gain in community understanding may come at the cost of accuracy and sensitivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al (2016) compare multiple methods of surveying tropical forest mammals in two reserves in Malaysia, revealing that sequencing blowfly-derived mammal DNA using HTS is a promising tool. Applying both metabarcoding via HTS and quantitative PCR (qPCR), Lacoursière-Roussel et al (2016) develop methods for the detection of amphibians and reptiles using aquatic environmental DNA (eDNA). With these groups being particularly threatened, it is important to be able to study their distributions and population health efficiently.…”
Section: Advances In Quantificationmentioning
confidence: 99%
“…Extracellular DNA fragments from the genomes of various micro‐ and macroorganisms (Hoffmann et al ) are found in nature and referred to as “environmental DNA (eDNA).” Techniques using eDNA to investigate the distribution and abundance/biomass of organisms have recently been developed for species inhabiting various habitats (Goldberg et al ; Thomsen and Willerslev ), including freshwater lentic (Ficetola et al ; Jerde et al ; Takahara et al ; Doi et al ; Dougherty et al ; Hänfling et al ) and lotic (Pilliod et al ; Fukumoto et al ; Deiner et al ; Ikeda et al ; Shaw et al ; Yamanaka and Minamoto ) systems and marine systems (Thomsen et al ; Miya et al ; Lacoursière‐Roussel et al ; Yamamoto et al ; Yamamoto et al ). The eDNA technique is likely to become a revolutionary tool used to increase both spatial and temporal scales for species‐distribution monitoring (Thomsen and Willerslev ).…”
mentioning
confidence: 99%